THE EFFECT OF USING COCOS NUCIFERA L. AS AN INCUBATOR FOR MAKING YOGHURT ON ORGANOLEPTIC TEST - M. M. H., MAKSUM; MIWADA, I N. S.; LINDAWATI, S. A. (Majalah Ilmiah Peternakan; Vol 23 No 3 (2020): Vol. 23 No. 3 (2020)DO - 10.24843/MIP.2020.v23.i03.p06, 2020)
This research was conducted to determine the value of organoleptic test on yoghurt incubated with different incubators. Conducted on January up to March 2020 at the Laboratory of Microbiology and Animal Product Technology Faculty of Animal Science, Udayana University. The experimental design is Completely Randomized Design by three treatments and five replications, those incubators are ordinary vacuum container (P0), green coconut (Cocos nucifera L.) without flesh (P1), and green coconut (Cocos nucifera L.) with flesh (P2). The variable observed is color, aroma, flavor, texture, and overall acceptances. The organoleptic test value analyzed using Kruskal Wallis test and if there some significantly differences (P<0,05), it would be continued by Mann-Whitney test. The result of panelists preference to the color, aroma, flavor, and overall acceptance of yoghurt in P0, P1, and P2 treatments showed no significant differences (P>0,05). The panelists preference to the texture of yoghurt was not significantly different (P>0,05) on P1 with P0, and P2 treatments, but P0 was significantly different (P<0,05) with the P2 treatment. This research can be concluded that the panelists preferred to the texture of yoghurt in P2 treatment. The green coconut (Cocos nucifera L.) with flesh (P2) gives the best value in the organoleptic test.